Why does de-radicalization seem a utopia? Evaluation on "Children of the Country" program - Hafid Algristian; Dian Dakwatul Choiriya; Diaz Syafrie Abdillah; Athiyatul Ulya; Hafizh Auliyan Sodali; Akbar Reza Muhammad; Handayani Handayani (AOSIS, 2019)
Children and adolescents are groups that are vulnerable to the radicalism influence. Curiosity and trial-error behaviour make them tend to do risk-taking behaviours. If it is not accompanied by good self-control ability, it will encourage them to do actions without thinking about the impact of these actions (impulsivity). If it is not accompanied by empathy, then it tends to be behaviour that opposes and disrupts the interests of others (aggressive behaviour). This study aimed to assess the "Children of the Country" program as an effort to de-radicalize children and adolescents. Quasi experimental study was used on 30 children and adolescents in a shelter of street children in Surabaya with a pretest/ post-test design. In order to measure the outcome of the program, a Radical Personality Test (RPT) was developed using big five personality construct. The increase of nationalism and positive behaviour score is not much to compensate the increase of negative radicalism score. This evaluation brings awareness to form a novel de-radicalization strategy for children and adolescents in the future.